2011
DOI: 10.1177/0021998311401938
|View full text |Cite
|
Sign up to set email alerts
|

Impact behavior of carbon fiber/epoxy composite manufactured by vacuum-assisted compression resin transfer molding

Abstract: Carbon fiber reinforced epoxy composites were successfully manufactured by a new compression resin transfer molding process. The main innovation is that the injection stage is vacuum assisted. The high fiber volume fraction and low void content are promising properties for structural applications. The samples were tested under instrumented falling weight impact loading. Based on the contact time and delamination plots, the damage initiation energy threshold has been found to be 1.42 J, and from the energy plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…At an impact energy of <10 J, only marginal fiber fracture and transverse cracks are observed in the impacted material, with no damage to the internal material. This result is different for composite laminates prepared by resin transfer molding . However, at an impact energy of <30 J, only fiber fracture and transverse crack failure are observed, with a relatively low crack depth and length.…”
Section: Analysis Of the Experimental Resultsmentioning
confidence: 77%
“…At an impact energy of <10 J, only marginal fiber fracture and transverse cracks are observed in the impacted material, with no damage to the internal material. This result is different for composite laminates prepared by resin transfer molding . However, at an impact energy of <30 J, only fiber fracture and transverse crack failure are observed, with a relatively low crack depth and length.…”
Section: Analysis Of the Experimental Resultsmentioning
confidence: 77%
“…Chang et al 13 discussed the influence of mold opening distance, injection pressure, compression pressure, preheated mold temperature, resin temperature, and cure temperature on the ultimate strength of CRTM parts and found that using a low compression pressure and high resin temperature were significant methods for improvements in the mechanical properties of the part. Aurrekoetxea et al 14 investigated the impact behavior of carbon fiber/epoxy composites made by vacuum-assisted CRTM and showed that a 30.25-J penetration energy threshold was deduced from the energy plot.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid composite molding (LCM) process with low-cost tooling, such as vacuum-assisted resin infusion molding (VARIM), has been widely used for large composite structures, including boat hull, wind turbine blade, and automobile chassis components. [4][5][6] However, its long cycle time makes it only be suitable for low and medium volumes of production. Accordingly, it has practical significance to shorten the cycle time of LCM process.…”
Section: Introductionmentioning
confidence: 99%